O plano de desenvolvimento institucional (PDI) como instrumento de gestão e aplicação de políticas públicas: um estudo em instituições públicas de ensino superior do estado do Paraná - Luz, Thasiana Maria Kukolj da (2014)
An Institutional Development Plan (IDP) is a document containing the essential part of strategic planning for institutions of higher education (IHE). An IDP must take in consideration public policies, institutional needs and society demands. Its basic structure is established by Decree 5.773/2006 and it guides the development of institutional planning and institutional and courses evaluation, as well as sets a north for the IHE. In order to assure its legitimacy, an IDP must rely on community involvement in all its phases, which can enhance social control, transparency and accountability to society. Community commitment grows when people engage in the process, making it easier to implement what is planned. This paper is aimed at analyzing the methodology employed in IHEs in the state of Paraná – Brazil for developing, implementing, supervising and evaluating an IDP, through applied and exploratory research. Multiple sources of evidence were used for data collection, such as documents, questionnaires, interviews and technical reports. Results show that improving academic community participation is still necessary, despite all the efforts made by sectors in charge. In addition to documentary analysis, questionnaires filled in by council members and interviews with those responsible for the IDP in IHEs led to the conclusion that it is necessary to strengthen and bring IDP closer to the academic community so that it can effectively bring the expected results. The study made it possible to understand how the IDP is conducted by these IHEs, showing the need to fully develop the employed methods and to improve communication channels with society.